Revised earthquake sources along Manila trench for tsunami hazard assessment in the South China Sea - Qiu, Qiang (2019)
Seismogenic tsunami hazard assessments are highly dependent on the reliability of earthquake source models. Here in a study of the Manila subduction zone (MSZ) system, we combine the geological characteristics of the subducting plate, geometry, and coupling state of the subduction interface to propose a series of fault rupture scenarios. We divide the subduction zone into three rupture segments: 14–16, 16–19, and 19–21.7∘ N inferred from geological structures associated with the down-going Sunda plate. Each of these segments is capable of generating earthquakes of a magnitude between Mw=8.5+ and Mw=9+, assuming a 1000-year seismic return period as suggested by previous studies. The most poorly constrained segment of the MSZ lies between 19 and 21.7∘ N, and here we use both local geological structures and characteristics of other subduction zone earthquakes around the world, to investigate the potential rupture characteristics of this segment. We consider multiple rupture modes for tsunamigenic earthquake and megathrust-splay fault earthquakes. These rupture models facilitate an improved understanding of the potential tsunami hazard in the South China Sea (SCS). Hydrodynamic simulations demonstrate that coastlines surrounding the SCS could be devastated by tsunami waves up to 10 m if large megathrust earthquakes occur in these segments. The regions most prone to these hazards include west Luzon of Philippines, southern Taiwan, southeastern China, central Vietnam, and Palawan Island.